2017
DOI: 10.1093/asj/sjx024
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an Integrated Biodimensional Method of Breast Augmentation with Anatomic, Highly Cohesive Silicone Gel Implants: Short-Term Results With the First 620 Consecutive Cases

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Montemurro et al reported a rotation rate of 3.0 percent to 3.6 percent per patient who underwent primary breast augmentation with macrotextured Allergan Style 410 implants, which is comparable to the rotation rate presented in this study. 7,10,18 These results do not indicate that the adhesive effect of Biocell macrotexturing makes them less likely to rotate compared with microtextured implants.…”
Section: Discussionmentioning
confidence: 78%
“…Montemurro et al reported a rotation rate of 3.0 percent to 3.6 percent per patient who underwent primary breast augmentation with macrotextured Allergan Style 410 implants, which is comparable to the rotation rate presented in this study. 7,10,18 These results do not indicate that the adhesive effect of Biocell macrotexturing makes them less likely to rotate compared with microtextured implants.…”
Section: Discussionmentioning
confidence: 78%
“…Baker grades III and IV are considered symptomatic and may require revisional surgery, including capsulectomy and implant exchange or removal. [35][36][37] Revision surgery often results in an inferior cosmetic outcome and a higher rate of repeat contracture recurrence, decreased patient satisfaction, and overall higher cost. 38,39 Numerous etiologies have been proposed for the formation of capsular contracture including immunological response to foreign body, surgical site infection, radiation therapy, implant type, incision type, and choice of pocket.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Numerous etiologies have been proposed for the formation of capsular contracture including immunological response to foreign body, surgical site infection, radiation therapy, implant type, incision type, and choice of pocket. 37,38,[40][41][42] However, the prevailing theory is that overt pocket infection or subclinical infection from implant contamination is the predominant cause. [43][44][45][46][47][48] Additionally, several of the theories probably include a component of predisposition to implant contamination (ie, incision placement).…”
Section: Discussionmentioning
confidence: 99%
“…See Figure 2 for an example of inframammary placement. The Akademikliniken method (AK or Q2), proposed by Per Hedén, addresses this issue through preoperative assessment of two distancesthe distance between the NAC and the IMF and vertical distance between the implant and the NAC (26,27). The ICE method, proposed by Mallucci and Branford, is a simplified, prospectively validated approach to inframammary incisionbased implants.…”
Section: E T H O D O L O G I E S S P E C I F I C T O S E L E C T I N ...mentioning
confidence: 99%